Isolation and characterization of an osmotic stress and ABA induced histone deacetylase in Arachis hygogaea - Liangchen, Su; Bin, Deng; Shuai, Liu; Limei, Li; Yuting, Zhong; Ling, Li (Frontiers in Plant Science, 2015)
Histone acetylation, which together with histone methylation regulates gene activity in response to stress, is an important epigenetic modification. There is an increasing research focus on histone acetylation in crops, but there is no information to date in peanut (Arachis hypogaea). We showed that osmotic stress and ABA affect the acetylation of histone H3 loci in peanut seedlings by immunoblotting experiments. Using RNA-seq data for peanut, we found a RPD3/HDA1-like superfamily histone deacetylase (HDAC), termed AhHDA1, whose gene is up-regulated by PEG-induced water limitation and ABA signaling. We isolated and characterized AhHDA1 from A. hypogaea, showing that AhHDA1 is very similar to an Arabidopsis HDAC (AtHDA6) and, in recombinant form, possesses HDAC activity. To understand whether and how osmotic stress and ABA mediate the peanut stress response by epigenetics, the expression of AhHDA1 and stress-responsive genes following treatment with PEG, ABA and the specific HDAC inhibitor trichostatin A (TSA) were analysed. AhHDA1 transcript levels were enhanced by all three treatments, as was expression of peanut transcription factor genes, indicating that AhHDA1 might be involved in the epigenetic regulation of stress resistance genes that comprise the responses to osmotic stress and ABA.